(4x+5)(4x-3)+(5-4x)(5+4x)=(3x-2)(3x+2)-(9x-5)(x+1)

Simple and best practice solution for (4x+5)(4x-3)+(5-4x)(5+4x)=(3x-2)(3x+2)-(9x-5)(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homewo

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x+5)(4x-3)+(5-4x)(5+4x)=(3x-2)(3x+2)-(9x-5)(x+1) equation:


Simplifying
(4x + 5)(4x + -3) + (5 + -4x)(5 + 4x) = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)

Reorder the terms:
(5 + 4x)(4x + -3) + (5 + -4x)(5 + 4x) = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)

Reorder the terms:
(5 + 4x)(-3 + 4x) + (5 + -4x)(5 + 4x) = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)

Multiply (5 + 4x) * (-3 + 4x)
(5(-3 + 4x) + 4x * (-3 + 4x)) + (5 + -4x)(5 + 4x) = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)
((-3 * 5 + 4x * 5) + 4x * (-3 + 4x)) + (5 + -4x)(5 + 4x) = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)
((-15 + 20x) + 4x * (-3 + 4x)) + (5 + -4x)(5 + 4x) = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)
(-15 + 20x + (-3 * 4x + 4x * 4x)) + (5 + -4x)(5 + 4x) = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)
(-15 + 20x + (-12x + 16x2)) + (5 + -4x)(5 + 4x) = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)

Combine like terms: 20x + -12x = 8x
(-15 + 8x + 16x2) + (5 + -4x)(5 + 4x) = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)

Multiply (5 + -4x) * (5 + 4x)
-15 + 8x + 16x2 + (5(5 + 4x) + -4x * (5 + 4x)) = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)
-15 + 8x + 16x2 + ((5 * 5 + 4x * 5) + -4x * (5 + 4x)) = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)
-15 + 8x + 16x2 + ((25 + 20x) + -4x * (5 + 4x)) = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)
-15 + 8x + 16x2 + (25 + 20x + (5 * -4x + 4x * -4x)) = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)
-15 + 8x + 16x2 + (25 + 20x + (-20x + -16x2)) = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)

Combine like terms: 20x + -20x = 0
-15 + 8x + 16x2 + (25 + 0 + -16x2) = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)
-15 + 8x + 16x2 + (25 + -16x2) = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)

Reorder the terms:
-15 + 25 + 8x + 16x2 + -16x2 = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)

Combine like terms: -15 + 25 = 10
10 + 8x + 16x2 + -16x2 = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)

Combine like terms: 16x2 + -16x2 = 0
10 + 8x + 0 = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)
10 + 8x = (3x + -2)(3x + 2) + -1(9x + -5)(x + 1)

Reorder the terms:
10 + 8x = (-2 + 3x)(3x + 2) + -1(9x + -5)(x + 1)

Reorder the terms:
10 + 8x = (-2 + 3x)(2 + 3x) + -1(9x + -5)(x + 1)

Multiply (-2 + 3x) * (2 + 3x)
10 + 8x = (-2(2 + 3x) + 3x * (2 + 3x)) + -1(9x + -5)(x + 1)
10 + 8x = ((2 * -2 + 3x * -2) + 3x * (2 + 3x)) + -1(9x + -5)(x + 1)
10 + 8x = ((-4 + -6x) + 3x * (2 + 3x)) + -1(9x + -5)(x + 1)
10 + 8x = (-4 + -6x + (2 * 3x + 3x * 3x)) + -1(9x + -5)(x + 1)
10 + 8x = (-4 + -6x + (6x + 9x2)) + -1(9x + -5)(x + 1)

Combine like terms: -6x + 6x = 0
10 + 8x = (-4 + 0 + 9x2) + -1(9x + -5)(x + 1)
10 + 8x = (-4 + 9x2) + -1(9x + -5)(x + 1)

Reorder the terms:
10 + 8x = -4 + 9x2 + -1(-5 + 9x)(x + 1)

Reorder the terms:
10 + 8x = -4 + 9x2 + -1(-5 + 9x)(1 + x)

Multiply (-5 + 9x) * (1 + x)
10 + 8x = -4 + 9x2 + -1(-5(1 + x) + 9x * (1 + x))
10 + 8x = -4 + 9x2 + -1((1 * -5 + x * -5) + 9x * (1 + x))
10 + 8x = -4 + 9x2 + -1((-5 + -5x) + 9x * (1 + x))
10 + 8x = -4 + 9x2 + -1(-5 + -5x + (1 * 9x + x * 9x))
10 + 8x = -4 + 9x2 + -1(-5 + -5x + (9x + 9x2))

Combine like terms: -5x + 9x = 4x
10 + 8x = -4 + 9x2 + -1(-5 + 4x + 9x2)
10 + 8x = -4 + 9x2 + (-5 * -1 + 4x * -1 + 9x2 * -1)
10 + 8x = -4 + 9x2 + (5 + -4x + -9x2)

Reorder the terms:
10 + 8x = -4 + 5 + -4x + 9x2 + -9x2

Combine like terms: -4 + 5 = 1
10 + 8x = 1 + -4x + 9x2 + -9x2

Combine like terms: 9x2 + -9x2 = 0
10 + 8x = 1 + -4x + 0
10 + 8x = 1 + -4x

Solving
10 + 8x = 1 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
10 + 8x + 4x = 1 + -4x + 4x

Combine like terms: 8x + 4x = 12x
10 + 12x = 1 + -4x + 4x

Combine like terms: -4x + 4x = 0
10 + 12x = 1 + 0
10 + 12x = 1

Add '-10' to each side of the equation.
10 + -10 + 12x = 1 + -10

Combine like terms: 10 + -10 = 0
0 + 12x = 1 + -10
12x = 1 + -10

Combine like terms: 1 + -10 = -9
12x = -9

Divide each side by '12'.
x = -0.75

Simplifying
x = -0.75

See similar equations:

| -6(x+y)=-6(360) | | 2(x-3)=6x-9 | | (4x+5)(4x-3)+(5-4x)(5+4x)=0 | | 100(0.06x+0.12y)=100(240)(0.09) | | 5(x+5)/6=3x-4 | | 3y-5x+4=0 | | 5n^2+16n+12=0 | | 5x^2-35x+60= | | 9n^2+16n+18=0 | | 6n-10=4n+16 | | (6x-2)(6x+2)= | | r18/49 | | 8(v+3)-2v=3(2v+3)-12 | | 1-3-7= | | -5+3+9= | | w/2-12h=53 | | w/2-12=53 | | (5x+2)(4x-y)= | | 19x+(-9)=-44+12x | | x^3-5x^3+3x+9=0 | | (c+8)(c+6)= | | x=18-(-2/9*y) | | x=18+2y/9 | | 1x+4/3x^2+11/3x^3 | | 3x^3-14x^2+12x=0 | | x+2=10-4x | | 22b+7b-4=180 | | 4+3x=2(-3x+7) | | -8(7-6x)=42 | | 8a-8=4.85+3a | | 60.95+13= | | 7176x=108x |

Equations solver categories